Implementasi Rasionalitas Instrumental sebagai Penyebab Krisis Kemanusiaan dalam Pengelolaan Sumber Daya Alam dan Lingkungan - Nirwana Langi; Sarjan Sarjan (Mataram University, 2026)
The development of modern rationality has brought rapid progress in science and technology, yet it has simultaneously generated ecological and humanitarian crises. This article aims to analyze how the implementation of instrumental rationality contributes to humanitarian crises in the management of natural resources and the environment. This study employs a descriptive qualitative method using a critical philosophical approach through a literature review of the works of Max Weber, Jürgen Habermas, and Hans Jonas. The analysis reveals that the dominance of instrumental rationality encourages humans to treat nature in an exploitative and anthropocentric manner, resulting in alienation and ecological degradation. As an alternative, communicative rationality and an ethics of ecological responsibility need to be developed to create a paradigm of resource management grounded in moral values, dialogue, and sustainability. This article emphasizes the importance of transforming human consciousness from a logic of efficiency toward an ethical and ecological rationality in order to safeguard the continuity of life on Earth.